2016
DOI: 10.1111/mpp.12506
|View full text |Cite
|
Sign up to set email alerts
|

Evolution, genomics and epidemiology of Pseudomonas syringae

Abstract: SUMMARYA remarkable shift in our understanding of plant-pathogenic bacteria is underway. Until recently, nearly all research on phytopathogenic bacteria was focused on a small number of model strains, which provided a deep, but narrow, perspective on plant-microbe interactions. Advances in genome sequencing technologies have changed this by enabling the incorporation of much greater diversity into comparative and functional research. We are now moving beyond a typological understanding of a select collection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(106 citation statements)
references
References 149 publications
(185 reference statements)
0
100
0
Order By: Relevance
“…These orthologs were concatenated and ClonalFrameML (Didelot and Wilson, 2015) was 609 used to identify recombination tracts that could inflate the branch length of members of the OTU as described 610 above. TMRCA of the OTU was estimated by calculating the mid-point-root to tip sequence divergence for a 611 representative of all 107 strains within OTU5, then dividing the median value of this distance by the neutral 612 substitution rate (Kimura, 1968) (we used here the point estimate of 8.7x10 -8 with our estimate of sd=6.0x10 -8 613 (McCann et al, 2017)). While we consider all sites (degenerate and non-degenerate) in the putatively non-614 recombined core, in addition to the fact that substitution rate is likely inaccurate for the longer timescale 615 analysed in the present study, both of these inaccuracies would likely lead to the underestimation of the age.…”
Section: Pan-genome Analysis and Phylogenetics 587mentioning
confidence: 99%
See 2 more Smart Citations
“…These orthologs were concatenated and ClonalFrameML (Didelot and Wilson, 2015) was 609 used to identify recombination tracts that could inflate the branch length of members of the OTU as described 610 above. TMRCA of the OTU was estimated by calculating the mid-point-root to tip sequence divergence for a 611 representative of all 107 strains within OTU5, then dividing the median value of this distance by the neutral 612 substitution rate (Kimura, 1968) (we used here the point estimate of 8.7x10 -8 with our estimate of sd=6.0x10 -8 613 (McCann et al, 2017)). While we consider all sites (degenerate and non-degenerate) in the putatively non-614 recombined core, in addition to the fact that substitution rate is likely inaccurate for the longer timescale 615 analysed in the present study, both of these inaccuracies would likely lead to the underestimation of the age.…”
Section: Pan-genome Analysis and Phylogenetics 587mentioning
confidence: 99%
“…These studies, which have observed a range of different patterns, are unfortunately 47 often limited to the historic strains that are available, and the conclusions vary for different collections, even of 48 the same pathogen species (Pirnay et al, 2009). 49Questions of pathogen epidemiology are of particular relevance when considering the genus 50Pseudomonas, which includes pathogens and commensals of both animals and plants (Baltrus et al, 2017) and is 51 (which was not peer-reviewed) is the author/funder. All rights reserved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…tomato DC3000 is required for virulence in planta in every pathogenic strain investigated so far, and its presence is strongly correlated with pathogenic potential on agriculturally relevant plants. On the other hand, the rhizobial system does not appear to be required for virulence in planta but was acquired via multiple horizontal gene transfers by strains within the P. syringae complex (Baltrus et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, its role in virulence remains elusive (Romanchuk et al 2014). Recently, Baltrus et al (2017) described four different Type Three Secretion Systems (T3SS) in P. syringae pathovars: canonical, rhizobial, single and atypical. The canonical system present in P. syringae pv.…”
Section: Introductionmentioning
confidence: 99%